Analisis Kepuasan Pengguna dalam Penerapan E-Procurement pada Divisi Supply Chain Management PT ASDP Indonesia Ferry (Persero) Kantor Pusat - Annadiyanti, Annisa Agni; Andrian, Rian (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to analyze the level of user satisfaction in the use of the E-Procurement system in the Supply Chain Management Division of PT. ASDP Indonesia Ferry (Persero) Head Office. The method used is quantitative with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach using SmartPLS 3.2.9 software. This approach is used to measure the relationship between latent variables that affect satisfaction, effectiveness, transparency, and accuracy of the E-Procurement system. The study population involved 30 people in the Supply Chain Management Division of the Head Office, with data collected through an online questionnaire using Google Form. The results showed that the use of E-Procurement can significantly reduce procurement costs and time, with a T-statistic value of 5.558 (> 1.96) and P < 0.05. However, this system does not increase transparency because its effect is not significant with a T-statistic value of 0.069 (<1.96). In addition, the implementation of E-Procurement also did not improve the accuracy of the procurement process, as indicated by the T-statistic value of 0.035 (<1.96). The main obstacles to implementation include limited user understanding, inadequate instructions, and poor data quality. This study concludes that although E-Procurement has the potential to improve efficiency, additional efforts such as intensive training, regulatory improvements, and better data management are needed to support its overall success.